SOIL QUALITY IN ORGANIC AGRICULTURAL LAND: STUDY OF CHEMICAL ANALYSIS AND SOIL MICROBIOLOGY - Melfa Aisyah Hutasuhut; Husnarika Febriani; Leni Widiarti (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2023)
Increased public awareness for a healthy diet must be balanced with successful cultivation. Organic farming system is the right choice since it leaves all non-organic components. This study aims to identify the chemical and microbiological properties of agricultural soils that apply organic systems located in Batang Buluh Village, Pematang Johar, Deli Serdang Regency, North Sumatra. Chemical analysis was carried out at Socfindo Laboratory in Medan, including testing the pH of H2O, total P and K, C Organic, N Kjehldahl, and CEC (Cation Exchange Capacity). Soil microbiological tests were carried out at Medan Regional Health Lab including gram staining tests and biochemical tests. The results of chemical analysis from the analysis of pH H2O, P and total K, Organic C, N Kjehldahl, and CEC (Cation Exchange Capacity) at the edges and middle each obtained that was pH 5 -6, soil total P content was 0.0260% up to 0.450%, available K analysis, namely 0.200% and 0.210%, organic C content obtained results of 0.970% and 0.630%, N content using the KJehldahl method was 0.150% and 0.090%, and CEC obtained results of 14.330 me/100 and 10.090 me/100 g. Related species of Bacillus contained in the soil were Gram-positive, rod-shaped, spore-forming, aerobic or facultative anaerobic, motile bacteria with peritrichous flagella.